Carbon Electrode Materials for Electrochemical Capacitors (review) - Myronyuk, I.F.; Mandzyuk, V.I.; Sachko, V.M. (Physics and Chemistry of Solid State, 2016)
The known methods of synthesis of carbon materials for electric symmetric electrochemical capacitors are considered. Particular attention is drawn to the methods of exo- and endotemplate synthesis of carbon materials. It is concluded that further improving of the electrochemical properties of the electrodes will be connected with the search for qualitatively new ways of carbon materials activation that provide microcrystallites a graphite-likestate and affinity of their surface to the electrolytes.